Comparative Insecticidal Effects of Dry Ocimum Gratissium (Scent Leaves) and Rambo™ Paper on Mosquitoes in Jos, Nigeria (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2021)
Insecticides are chemicals or biological substances that are used to kill or disable insects. Blood feeding mosquitoes are responsible for the intolerable biting nuisance and transmission of large number of diseases such as malaria, yellow fever, dengue fever, filarias is amongst others, causing serious health problems to humans and obstacles to socioeconomic development of developing nations like Nigeria. The insecticidal effect of scent leaves (Ocimum gratissum) and Rambo™ paper on mosquitoes was investigated. The study is aimed at comparing the insecticidal effects of Ocimum gratissimum and Rambo™ paper on mosquitoes in Jos. 100 mosquitoes were exposed to dried Ocimum gratissum and Rambo™ paper at different time intervals of 5, 10 and 12 min. Results obtained showed a time dependent insecticidal effect on mosquitoes, which was 54.2%, 54.0% and 55.6% total mortality of mosquitoes at respective time intervals on exposures to both Rambo™ paper insecticide and Osimum gratissum, indicating that there was a significant difference in the lethal effect of Rambo™ paper insecticide and scent leave on mosquitoes at (p
Keywords: Ocimum grasstisimum; Mosquitocidal; Insecticidal; Rambo™ paper; Malaria eradication